Integrated Physiologic Assessment of Ischemic Heart Disease in Real-World Practice Using Index of Microcirculatory Resistance and Fractional Flow Reserve: Insights From the International Index of Microcirculatory Resistance Registry. (November 2015) - Lee, Joo Myung; Layland, Jamie; Jung, Ji-Hyun; Lee, Hyun-Jung; Echavarria-Pinto, Mauro; Watkins, Stuart; Yong, Andy S.; Doh, Joon-Hyung; Nam, Chang-Wook; Shin, Eun-Seok; Koo, Bon-Kwon; Ng, Martin K.; et al.
Abstract : Background—: The index of microcirculatory resistance (IMR) is a quantitative and specific index for coronary microcirculation. However, the distribution and determinants of IMR have not been fully investigated in patients with ischemic heart disease (IHD). Methods and Results—: Consecutive patients who underwent elective measurement of both fractional flow reserve (FFR) and IMR were enrolled from 8 centers in 5 countries. Patients with acute myocardial infarction were excluded. To adjust for the influence of collateral flow, IMR values were corrected with Yong's formula (IMRcorr ). High IMR was defined as greater than the 75th percentile in each of the major coronary arteries. FFR⩽0.80 was defined as an ischemic value. 1096 patients with 1452 coronary arteries were analyzed (mean age 61.1, male 71.2%). Mean FFR was 0.84 and median IMRcorr was 16.6 U (Q1, Q3 12.4 U, 23.0 U). There was no correlation between IMRcorr and FFR values ( r =0.01, P =0.62), and the categorical agreement of FFR and IMRcorr was low (kappa value=−0.04, P =0.10). There was no correlation between IMRcorr and angiographic % diameter stenosis ( r =−0.03, P =0.25). Determinants of high IMR were previous myocardial infarction (odds ratio [OR] 2.16, 95% confidence interval [CI] 1.24–3.74, P =0.01), right coronary artery (OR 2.09, 95% CI 1.54–2.84, P <0.01), female (OR 1.67, 95% CI 1.18–2.38, P <0.01), and obesity (OR 1.80, 95% CI 1.31–2.49, P <0.01). Determinants of FFR ⩽0.80 were left anterior descending coronary artery (OR 4.31, 95% CI 2.92–6.36, P <0.01), angiographic diameter stenosis ≥50% (OR 5.16, 95% CI 3.66–7.28, P <0.01), male (OR 2.15, 95% CI 1.38–3.35, P <0.01), and age (per 10 years, OR 1.21, 95% CI 1.01–1.46, P =0.04). Conclusions—: IMR showed no correlation with FFR and angiographic lesion severity, and the predictors of high IMR value were different from those for ischemic FFR value. Therefore, integration of IMR into FFR measurement may provide additional insights regarding the relative contribution of macro- and microvascular disease in patients with ischemic heart disease. Clinical Trial Registration—: URL:http://www.clinicaltrials.gov . Unique identifier: NCT02186093. Abstract : Supplemental Digital Content is available in the text.